Transformation of Counseling Services in Helping Students Adapt to the Independent Curriculum - Rike Ernawati Sinaga; Firman; Neviyarni S; Muhammad Asyraf Che Amat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The implementation of Merdeka Curriculum provides new challenges in education, especially for students who must adapt to project-based learning and a more flexible approach. In this context, Guidance and Counseling (BK) services play a strategic role in supporting students to overcome adaptation challenges while optimizing their potential. This research uses the literature study method to analyze the BK service transformation strategies that are relevant to the needs of the Merdeka Curriculum. Data sources include research articles, policy documents, and reports related to the implementation of the Merdeka Curriculum and the role of counseling services in schools. The results showed that BK services need to be transformed through technology-based approaches, such as online counseling, student needs surveys, and collaboration between BK teachers, subject teachers, and parents. Other recommended strategies are improving the professional competence of counseling teachers through continuous training and strengthening the integration of counseling services with the dimensions of the Pancasila Student Profile. The implementation of these strategies not only helps students adapt to Merdeka Curriculum but also contributes to improving students' independence skills, creativity, and critical thinking ability. With an innovative and collaboration-based approach, counseling services can be a catalyst in creating a learning ecosystem that is more adaptive and supports the maximum development of student potential.